2018
DOI: 10.1159/000492026
|View full text |Cite
|
Sign up to set email alerts
|

How Does Continuous Renal Replacement Therapy Affect Septic Acute Kidney Injury?

Abstract: Sepsis is the leading cause of acute kidney injury (AKI) in the intensive care unit. As the most common treatment of septic AKI, it is believed that continuous renal replacement therapy (CRRT) can not only maintain the water balance and excrete the metabolic products but also regulate the inflammation and promote kidney recovery. CRRT can remove the inflammatory cytokines to regulate the metabolic adaption in kidney and restore the kidney recovery to protect the kidney in septic AKI. Second, CRRT can provide e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 50 publications
0
24
0
1
Order By: Relevance
“…This study shows that PaO 2 /FiO 2 of the children can reach 200 mmHg at 12 h and more than 300 mmHg at 24 h. The results showed that CRRT could improve tissue oxygenation and metabolism of sepsis-related AKI neonates by eliminating pulmonary interstitial edema, improving microcirculation and increasing the oxygen uptake capacity of parenchymal cells. Zhang et al [19] research has shown that CRRT could not only maintain fluid balance in vivo, excrete metabolites, but also clear inflammatory factors and promote renal recovery. The mechanism of CRRT in the treatment of sepsis-related AKI is as follows [20][21][22], CRRT can regulate renal metabolic adaptation and restoring renal function.…”
Section: Discussionmentioning
confidence: 99%
“…This study shows that PaO 2 /FiO 2 of the children can reach 200 mmHg at 12 h and more than 300 mmHg at 24 h. The results showed that CRRT could improve tissue oxygenation and metabolism of sepsis-related AKI neonates by eliminating pulmonary interstitial edema, improving microcirculation and increasing the oxygen uptake capacity of parenchymal cells. Zhang et al [19] research has shown that CRRT could not only maintain fluid balance in vivo, excrete metabolites, but also clear inflammatory factors and promote renal recovery. The mechanism of CRRT in the treatment of sepsis-related AKI is as follows [20][21][22], CRRT can regulate renal metabolic adaptation and restoring renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines are molecules that dissolve in water and are in free form in circulation. Their molecular weight is between 0.5-60 kDa (10). RRT filters are semi-permeable membranes with approximately 35 kDa pores (11).…”
Section: Introductionmentioning
confidence: 99%
“…Continuous renal replacement therapy (CRRT) with improvement in extracorporeal blood purification techniques and membrane materials are widely used in critical illness(10). The theoretical cut-off for an RRT membrane is about 35 kDa.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sepsis is the most common cause of acute kidney injury (AKI) in intensive care patients and an independent predictor of poor outcome [17]. Continuous renal replacement therapy (CRRT) is a standard to preserve hemodynamic stability.…”
Section: Introductionmentioning
confidence: 99%